Functional Compartmentalization of the Contribution of Hippocampal Subfields to Context-Dependent Extinction Learning - Méndez-Couz, Marta; Becker, Jana M.; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2019)
During extinction learning (EL), an individual learns that a previously learned behavior no longer fulfills its original purpose, or is no longer relevant. Recent studies have contradicted earlier theories that EL comprises forgetting, or the inhibition of the previously learned behavior, and indicate that EL comprises new associative learning. This suggests that the hippocampus is involved in this process. Empirical evidence is lacking however. Here, we used fluorescence in situ hybridization of somatic immediate early gene (IEG) expression to scrutinize if the hippocampus processes EL. Rodents engaged in context-dependent EL and were also tested for renewal of (the original behavioral response to) a spatial appetitive task in a T-maze. Whereas distal and proximal CA1 subfields processed both EL and renewal, effects in the proximal CA1 were more robust consistent with a role of this subfield in processing context. The lower blade of the dentate gyrus and the proximal CA3 subfields were particularly involved in renewal. Responses in the distal and proximal CA3 subfields suggest that this hippocampal subregion may also contribute to evaluation of the reward outcome. Taken together, our findings provide novel and direct evidence for the involvement of distinct hippocampal subfields in context-dependent EL and renewal.